A CONVERSATION ANALYSIS OF REPAIR STRATEGIES IN INDONESIAN ELEMENTARY EFL STUDENTS - Tita Novitasari, - (2020)
This study aimed to investigate the types of repair strategies and techniques of repair initiation used by Indonesian Elementary EFL students during the classroom interaction with their teacher. The participants were Elementary EFL students at the beginner level. By using qualitative research, the study used four types of repair strategies by Schegloff, Jefferson, and Sacks (1977) and techniques of repair initiation from Finegan (2008). The data sources were in the form of video recorded of classroom interactions that were transcribed by applying Jefferson Transcription Notation (2004). The findings of the study revealed that the students used all types of repair strategies. The most frequently is OISR which obtained 23 occurrences (37.1%). Besides, the three techniques were found in the conversation. Asking question toward the problem is the dominant one which occurred 31 (50.0%). Another technique was revealed which is giving possible understanding toward the problem. The results of the present study indicate that the speakers produced the trouble source more which affected the recipient to initiate asking for the repair. It means that the trouble source identified by the teacher, but the students did the repair. The trouble source that appeared was affected by the students' proficiency and the lack of knowledge that they had toward the topic. Also, the teachers initiated asking for explanation to raise the students' ability in terms of their English knowledge and speaking fluency. However, the teacher should consider that the students should have a chance to repair their trouble source or problem by themselves.